2007
DOI: 10.1161/circulationaha.107.183689
|View full text |Cite
|
Sign up to set email alerts
|

Reprint

Abstract: Purpose-The aim of this statement is to present current and comprehensive recommendations for the diagnosis and treatment of acute spontaneous intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(77 citation statements)
references
References 208 publications
2
73
1
1
Order By: Relevance
“…Of the patients who survive, 80% will be unable to function independently at 6 months poststroke 2, 3. The initial tissue injury of ICH activates numerous secondary injury pathways, including the release of toxic hemolysis products, enhanced oxidative stress, and robust proinflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Of the patients who survive, 80% will be unable to function independently at 6 months poststroke 2, 3. The initial tissue injury of ICH activates numerous secondary injury pathways, including the release of toxic hemolysis products, enhanced oxidative stress, and robust proinflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) is one of the most devastating forms of stroke [1]. Observational studies have reported a modest but important risk of early seizure following ICH.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have reported a modest but important risk of early seizure following ICH. [2,3] Due to this risk, consideration of prophylactic antiepileptic drug (AED) use is recommended for patients with lobar hemorrhage in current guidelines for management of ICH [1,4]. However, it is not clear that seizures worsen outcome from ICH and there is evidence that AEDs may impair recovery in patients with other types of brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines for the management of spontaneous ICH were published in 1999 ( n = 15), 2007 ( n = 23), and 2010 ( n = 11), with the last one being the most-cited article annually [4, 15, 16]. It is notable that the most recent guidelines were cited more frequently, which can be attributed to ­physicians considering the evidence-based guidelines when treating patients nowadays.…”
Section: Discussionmentioning
confidence: 99%